GE_GERICHTE P/19322/2018 vom 23. November 2018 - GE Cour de justice (2018)
CLASSEMENT DE LA PROCÉDURE ; ASSISTANCE JUDICIAIRE ; VOIES DE FAIT ; CAS BÉNIN ; IN DUBIO PRO DURIORE | CPP.310; CPP.136; CPP.125; CP.52